(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
Objective: Otitis Media with effusion (OME) is a vital and common problem in school going children. It is the prime cause of impaired hearing and social trouble in children which has long term impact on speech and language development. Enlarged Adenoid is a very common causative factor in the development of OME. The aim of this study is to observe the ground of the disease in favour of correction of effusion after adenoidectomy. Methods: This is a prospective descriptive study had been carried out in BIRDEM General Hospital from January 2012 to December 2015. A total 40 patients aged 3 to 12 years old who had adenoid hypertrophy and OME, confirmed with pre operative X-ray nasopharynx lateral view, PTA and tympanometry were included in this study. All patients underwent adenoidectomy under General anaesthesia. Follow up was done with PTA and tympanometry at 3rd months after operation. Result: Among 80 ears of 40 patients, pre operative tympanometry showed type B curve in 43.2% of ears. Post operative audiometric assessment showed mean hearing gain at 3rd month being 5.32 dB. At 3rd month follow up, 20 ears had type A curve, only 6 ears had type B curve and 53 ears had type C curve. Conclusion: So, adenoidectomy is an effective operation in correcting middle ear effusion and resulting hearing improvement as well as speech and language development in children with enlarged adenoid and OME. Bangladesh J Otorhinolaryngol; April 2017; 23(1): 67-73